A key role for scientists in strengthening the Biological Weapons Convention - Shang, Lijun; Sheff, Lincoln; Dando, Malcolm (Frontiers in Political Science, 2023)
It is not easy to be optimistic about international security at the present time, but 9th Review Conference of the Biological Weapons Convention in December 2022 agreed a renewed effort to strengthen the Convention after decades of stagnation. In March 2023 an agreement was also reached on an agenda and timetable for this effort over the next 2 years. Scientists have a long history of providing valuable input to such meetings, in this paper, we discuss how such input might best be provided with complicated challenges now facing the BWC and concluded that there is much that could be done, but greater coordination amongst scientists is needed.